KEMAMPUAN GURU DALAM PERENCANAAN DAN PELAKSANAAN PEMBELAJARAN SERTA PENGARUHNYA TERHADAP PROBLEMATIKA BELAJAR MATEMATIKA SISWA - Yesi Ismawati; Fina Hanifa Hidayati (Jurnal Karya Pendidikan Matematika, 2020)
A teacher’s skill is a teacher's ability to manage a learning process and ensure learners achieve learning goal. In mathematics learning, an important thing that must be mastered by teacher is the ability to design a plan of learning and execute it in the classroom. This study aims to determine the ability of teachers in designing and implementing the learning of mathematics and knowing its effect on the problems faced by students during the process of learning. The method that is used is the qualitative approach with the technique of data collection through observation, interviews , and documentation. The results showed that (1) the ability of the teachers in terms of planning and implementation of mathematics learning is still lacking, (2) there is a mismatch between planning and implementation of learning, and (3) there are learning problems such as fault concept, ineffective learning time, and less active students during mathematics learning.